Quality of life in multiple sclerosis and other chronic autoimmune and non-autoimmune diseases (2009)
Introduction. Diseases that involve the nervous system and the musculoskeletal system are particularly likely to produce different limitations and deficits, and to affect the individual conception of quality of life. Aim. To determine the impact on quality of life generated by chronic autoimmune diseases like multiple sclerosis (MS), rheumatoid arthritis (RA), systemic lupus erythematosus (SLE), Sjogren's syndrome (SS), ankylosing spondylitis (AS) and chronic musculotendinous diseases like osteoarthritis (OA) and fibromyalgia (FM), using the Short Form 36-item (SF-36) health questionnaire. Patients and methods. A descriptive cross-sectional study was conducted between January 2004 and June 2006 and included 509 individuals, of whom 56 had MS, 36 SS, 24 AS, 200 RA, 65 SLE, 54 OA and 74 FM. Guided interviews were conducted to evaluate each sphere of the SF-36 health questionnaire. The statistical analysis was performed using the general lineal model, with means differences according to each diagnosis. Results. Compared to patients with RA, those with MS showed significant differences in the physical functioning and social functioning dimensions. The lowest score was recorded in those with FM, except in physical functioning, where MS had the lowest mean. No differences were found in the mean scores on general conception of the state of health in each condition analysed. Conclusions. Different neurological functions deteriorate progressively in MS, which has repercussions on the musculoskeletal system; this leads to a poorer quality of life, mainly in the physical and social functions. The disability generated is not only defined by deficit but also by the degrees of functional limitation within the context of personal health. Quality of life thus becomes a global biopsychosocial phenomenon. © 2009, REVISTA DE NEUROLOGÍA.